Marine mammals of the world : - Jefferson, Thomas A. (Elsevier, 2008)
With coverage on all the marine mammals of the world, authors Jefferson, Webber, and Pitman have created a user-friendly guide to identify marine mammals alive in nature (at sea or on the beach), dead specimens in hand, and also to identify marine mammals based on features of the skull. This handy guide provides marine biologists and interested lay people with detailed descriptions of diagnostic features, illustrations of external appearance, beautiful photographs, dichotomous keys, and more. Full color illustrations and vivid photographs of every living marine mammal species are incorporated, as well as comprehendible maps showing a range of information. For readers who desire further consultation, authors have included a list of literature references at the end of each species account. For an enhanced understanding of habitation, this guide also includes recognizable geographic forms described separately with colorful paintings and photographs. All of these essential tools provided make Marine Mammals of the World the most detailed and authoritative guide available! * Contains superb photographs of every species of marine mammal for accurate identification * Authors collective experience adds up to 80 years, and have seen nearly all of the species and distinctive geographic forms described in the guide * Provides the most detailed and anatomically accurate illustrations currently available * Special emphasis is placed on the identification of species in problem groups, such as the beaked whales, long-beaked oceanic dolphin, and southern fur seals * Includes a detailed list of sources for more information at the back of the book